2020
DOI: 10.5935/0103-507x.20200036
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among healthcare professionals in intensive care units: a cross-sectional population-based study

Abstract: Objective To assess the prevalence of and factors associated with Burnout syndrome among intensive care unit professionals. Methods In this cross-sectional population-based study, a questionnaire assessing sociodemographic, behavioral, and occupational data was administered to 241 nurses and physicians working in 17 public intensive care units in São Luis (MA), Brazil. The Maslach Burnout Inventory - Human Services Survey was used to identify Burnout syndrome based on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
2
15
0
16
Order By: Relevance
“…The prevalence of burnout varies depending on the country where the research was carried out. Two studies carried out in Brazil showed disparate results, in one low level of burnout, in all its dimensions [ 25 ], and in the other, a high prevalence of burnout [ 19 ]. In another study carried out in India, most of the participants obtained a high level in the three dimensions established by the Maslach questionnaire [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of burnout varies depending on the country where the research was carried out. Two studies carried out in Brazil showed disparate results, in one low level of burnout, in all its dimensions [ 25 ], and in the other, a high prevalence of burnout [ 19 ]. In another study carried out in India, most of the participants obtained a high level in the three dimensions established by the Maslach questionnaire [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Atualmente, quando se fala sobre doenças laborais, logo vem à palavra "burnout" na discussão; essa associação ocorre como consequência da elevada prevalência dessa síndrome entre os trabalhadores; mostrando a associação entre a prática do trabalho e o burnout (Porciuncula, Venâncio & Silva, 2020;Alvares, et al, 2020).…”
Section: Introductionunclassified
“…Entretanto, nem sempre estes mecanismos são suficientes para o enfrentamento dessas situações e o trabalhador de saúde pode sofrer algumas mudanças em especial do humor, o qual pode ser indício de depressão ou um humor mais irritável e Síndrome de Bornout (7) . Síndrome de Burnout, não tem uma definição precisa, mas existe um entendimento em considerar que surge no indivíduo como um feedback ao estresse laboral (8) . Ela fica definida (6,8,9) .…”
Section: Introductionunclassified
“…Síndrome de Burnout, não tem uma definição precisa, mas existe um entendimento em considerar que surge no indivíduo como um feedback ao estresse laboral (8) . Ela fica definida (6,8,9) . Essa patologia é decorrente de exaustão, desapontamento e ausência de interesse pela atividade de trabalho que aparece nas profissões que trabalham em comunicação direta com pessoas (8) .…”
Section: Introductionunclassified
See 1 more Smart Citation